The statistical analysis of the radioactivity concentration of the water data in malatya city, Turkey - Do?ru, Mahmut; Yalçin, Mesut; Külahci, Fatih; Canbazo?lu, Cumhur; Baykara, Oktay (Elsevier Ltd, 2005)
[Abstract Not Available]